Financial security of the banking system of Ukraine under the conditions of martial state: classification of possible threats - Kryshtal, Halyna (Management and Entrepreneurship: Trends of Development, 2023)
The purpose of the article is to determine the modern direction of ensuring the financial security of the banking system of Ukraine in the conditions of martial law in terms of identifying and classifying possible threats. The author’s interpretation of the concept of "financial security of the banking system in the conditions of digitization and the state of war in the country" is proposed, which takes into account the processes of digitalization of the financial sphere. This means that the definition of this concept not only takes into account traditional aspects of security, but also takes into account new requirements and opportunities that arise with the growing use of modern technologies. The author provided recommendations for calculating the bank’s financial security, which opens up new opportunities for further research and improvement of assessment methods in the field of banking security. This can become the basis for practical application in the activities of each bank, providing optimal strategies and measures to ensure financial stability and protection against new forms of threats. The theoretical and methodological basis of the research is based on the study of the scientific works of leading scientists in the field of banking, as well as on the own interpretation of the classification of possible threats aimed at the financial security of the banking system of Ukraine. In the course of the research, such methods as analysis and synthesis, methods of historical and logical modeling were used. From a practical point of view, the research includes the method of grouping statistical data, statistical and econometric analysis. These approaches are aimed at creating a comprehensive understanding of the financial security of the banking system of Ukraine and determining the optimal protection strategies. JEL Classification: E50; G 21; G32.